EDITORIAL TEAM - Selangga, Dewa Gede Wiryangga (International Journal of Biosciences and Biotechnology; Vol 8 No 1 (2020): Vol. 8 No. 1, September 2020, 2020)
INTERNATIONAL JOURNAL OF BIOSCIENCES AND BIOTECHNOLOGY  VOL. 8 NO. 1 • SEPTEMBER 2020  CHIEF EDITOR: Prof. I Gede Putu Wirawan, Ph.D (Udayana University, Indonesia) E-mail: igpwirawan@unud.ac.id  MANAGING DIRECTOR: Putu Sudiarta, Ph.D. (Udayana University, Bali-Indonesia) E-mail: putusudiarta@unud.ac.id Dewa Gede Wiryangga Selangga, M.Si (Udayana University, Bali-Indonesia) E-mail: dewanggaselangga@gmail.com  EDITORS: Dr. Ayu Dewi (Udayana Universit y, Bali-Indonesia) - E-mail: ay u.dewi@unud.ac.id Prof. Dr. Masahiro Nogawa ( Shinshu Universit y, Japan) - E-mail: mnogawa@shinshu-u.ac.id Prof. Dr. Acram Taji (Queensland Universit y o f Techno logy, Australia) - E-mail: acram .taji@qut.edu.au Jennifer Firn, Ph.D. (Queensland University of Technology, Australia) - E-mail: jennife r.firn@qut.edu.au Prof. Dr. Hee Wan Kang (Hankyo ng National Universit y, Korea) - E-mail: kanghw2@hknu.ac.kr Prof. Dr. Ir. Rindang Dwiyani, M.Sc. (Udayana University, Bali-Indonesia) Email: rindangdwiyani@unud.ac.id Dr. Listihani (Mahasaraswati University, Bali-Indonesia) Email: listihani9@gmail.com Dr. Kahar Muzakar (Universit y of Jember, Indonesia) - E-mail: kaharmzk@unej.ac. id Dr. Anna Kurdyavtseva – (Engelhardt Institute of Molecular Bio logy, Russian Academy of Sciences), E-mail: rhizamoeba@mail.ru Prof. Dr. Nataliya Shchego lkova – Lo monosov Moscow State Universit y, Russia - E-mail: nshegolkova@gmail.co m    TECHNICAL EDITORS Dr. Ir. Ni Nyo man Ari Mayadewi, M.P. I Gede Wahyu Pramartha, S.Kom.  LAYOUT DESIGNER I Gede Wahyu Pramartha, S.Kom.  PUBLISHERS: Facult y of Agriculture, Udayana Universit y in cooperation with Asia Oceania Bioscience and Biotechno logy Consortium (AOBBC)  ADDRESS:  Central Laboratory for Genetic Resource and Molecular Biology Udayana University Postgraduate Building, 3rd Floor Jl.PB Sudirman, Denpasar-Bali, Indonesia E-mail : ijbb@unud.ac.id  Telp.+62-811387389; +62-81339507478